174k views
1 vote
( − √ 5 , 0 ) ( 0 , √ 7 ) step by step using distance formula

User Sukhmel
by
5.6k points

1 Answer

5 votes


\bf ~~~~~~~~~~~~\textit{distance between 2 points} \\\\ (\stackrel{x_1}{-√(5)}~,~\stackrel{y_1}{0})\qquad (\stackrel{x_2}{0}~,~\stackrel{y_2}{√(7)})\qquad \qquad d = √(( x_2- x_1)^2 + ( y_2- y_1)^2) \\\\\\ d=\sqrt{[0-(-√(5))]^2+[√(7)-0]^2}\implies d = \sqrt{(0+√(5))^2+(√(7)-0)^2} \\\\\\ d = \sqrt{(√(5))^2+(√(7))^2}\implies d = √(5+7)\implies d = √(12)\implies d \approx 3.464

User Lord Bo
by
6.3k points